Chloride channel inhibition by a red wine extract and a synthetic small molecule prevents rotaviral secretory diarrhoea in neonatal mice. Issue 7 (19th September 2013) - Ko, Eun-A; Jin, Byung-Ju; Namkung, Wan; Ma, Tonghui; Thiagarajah, Jay R; Verkman, A S
Abstract : Background: Rotavirus is the most common cause of severe secretory diarrhoea in infants and young children globally. The rotaviral enterotoxin, NSP4, has been proposed to stimulate calcium-activated chloride channels (CaCC) on the apical plasma membrane of intestinal epithelial cells. We previously identified red wine and small molecule CaCC inhibitors. Objective: To investigate the efficacy of a red wine extract and a synthetic small molecule, CaCCinh -A01, in inhibiting intestinal CaCCs and rotaviral diarrhoea. Design: Inhibition of CaCC-dependent current was measured in T84 cells and mouse ileum. The effectiveness of an orally administered wine extract and CaCCinh -A01 in inhibiting diarrhoea in vivo was determined in a neonatal mouse model of rotaviral infection. Results: Screening of ∼150 red wines revealed a Cabernet Sauvignon that inhibited CaCC current in T84 cells with IC50 at a ∼1:200 dilution, and higher concentrations producing 100% inhibition. A >1 kdalton wine extract prepared by dialysis, which retained full inhibition activity, blocked CaCC current in T84 cells and mouse intestine. In rotavirus-inoculated mice, oral administration of the wine extract prevented diarrhoea by inhibition of intestinal fluid secretion without affecting rotaviral infection. The wine extract did not inhibit the cystic fibrosis chloride channel (CFTR) in cell cultures, nor did it prevent watery stools in neonatal mice administered cholera toxin, which activates CFTR-dependent fluid secretion. CaCCinh -A01 also inhibited rotaviral diarrhoea. Conclusions: Our results support a pathogenic role for enterocyte CaCCs in rotaviral diarrhoea and demonstrate the antidiarrhoeal action of CaCC inhibition by an alcohol-free, red wine extract and by a synthetic small molecule.